Simulation study for the energy and position reconstruction performances of the beam monitoring system of Carbon Ion Radiation Therapy using GEANT4 - Yun Eo; Na Hye Kwon; Joonsuk Bae; Byunggu Cheon; Guk Cho; Suyong Choi; Hyunsuk Do; Seungkyu Ha; Changgi Huh; Kyuyeong Hwang; Haeun Jang; Seoyun Jang; et al. (PLoS ONE, 2025)
Carbon Ion Radiation Therapy is operated in several countries because of its advantage to have high dose concentration and/or high linear energy transfer (LET). To estimate the beam performance of Carbon Ion Radiation Therapy, we target the 1% energy and 1 mm2 position resolutions of the beam monitoring system. The beam monitoring system consists of a scintillation crystal and fiber hodoscope. The scintillation crystal is 20 × 20 × 120mm3 and its candidates are LYSO, CsI and BGO. The fiber hodoscope is composed of 1 mm thickness scintillation fibers and the fibers are arranged vertically for 2D reconstruction. With GEANT4 simulation, we verify the performance of our beam monitoring system. The energy response of the LYSO and BGO scintillators is linear within ± 2%. The energy resolution of each crystal candidate achieves the goal; LYSO (0.061%), CsI (0.20%) and BGO (0.10%). The position is reconstructed via fiber hodoscope within 5% uncertainty.